The important activity of the Dental Materials subject: An experience report (Research, Society and Development, 2023)
Academic tutoring is an educational support program offered to university students who wish to deepen their knowledge of certain subjects, helping to improve the teaching-learning process. The aim of this paper is to present a report on the experience of tutoring in the subject of Dental Materials, at a University Center located in Viçosa-MG, offered to students on the Dentistry course, demonstrating the importance of tutoring in the teaching-learning process. This is a descriptive experience report based on the experiences of academic tutoring in the subject of Dental Materials, highlighting how tutoring contributes to the learning of the students being tutored and also to the development of the tutors themselves, helping to shape and consolidate the content. The tutoring program provided greater theoretical and practical knowledge of the subject, as evidenced by the pass rate and class performance. It was also an opportunity for personal and professional growth for the monitor, as it sparked an interest in teaching in the academic world.